2022
DOI: 10.1002/jbio.202200018
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional thermophotonic image optimization modalities of truncated correlation photothermal coherence tomography

Abstract: Truncated correlation photothermal coherence tomography (TC-PCT) is a pulse-compression, matched-filter-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The eTC-PCT software then generates the time/equivalent depth profile of photothermal properties from its primary output channels, which are the amplitude and phase. The detailed explanation of the eTC-PCT signal processing technique can be found elsewhere. , Here, eTC-PCT images are used to compare the differences in the morphology of solvent and melt mixing samples (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eTC-PCT software then generates the time/equivalent depth profile of photothermal properties from its primary output channels, which are the amplitude and phase. The detailed explanation of the eTC-PCT signal processing technique can be found elsewhere. , Here, eTC-PCT images are used to compare the differences in the morphology of solvent and melt mixing samples (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed explanation of the eTC-PCT signal processing technique can be found elsewhere. 48,49 Here, eTC-PCT images are used to compare the differences in the morphology of solvent and melt mixing samples (Figure 5).…”
Section: Thermal Conductivity and Heat Dissipationmentioning
confidence: 99%
“…The recent development of thermophotonic modalities such as truncated correlation photothermal coherence tomography (TC-PCT) (5) and its enhanced version (eTC-PCT) (6) has the ability to produce depth-resolved tomographic images and three-dimensional (3D) mapping of biological hard and soft tissues. In dental imaging applications, eTC-PCT has shown 3D visualization and the subsurface extent of a variety of dental defects validated by micro-computed tomography (μCT), a nondestructive laboratory gold standard method for the measurement of dental flaws and demineralization caries (7)(8)(9)(10). These proof-of-concept studies demonstrated that eTC-PCT has the potential to provide dental practitioners not only with tools for detecting caries but also for detecting cracks before a large portion of a tooth fractures off, in their future clinical applications.…”
Section: Introductionmentioning
confidence: 99%